Recent Advances in Nanomaterials Used for Wearable Electronics - Minye Yang; Zhilu Ye; Yichong Ren; Mohamed Farhat; Pai-Yen Chen (Micromachines, 2023)
In recent decades, thriving Internet of Things (IoT) technology has had a profound impact on people’s lifestyles through extensive information interaction between humans and intelligent devices. One promising application of IoT is the continuous, real-time monitoring and analysis of body or environmental information by devices worn on or implanted inside the body. This research area, commonly referred to as wearable electronics or wearables, represents a new and rapidly expanding interdisciplinary field. Wearable electronics are devices with specific electronic functions that must be flexible and stretchable. Various novel materials have been proposed in recent years to meet the technical challenges posed by this field, which exhibit significant potential for use in different wearable applications. This article reviews recent progress in the development of emerging nanomaterial-based wearable electronics, with a specific focus on their flexible substrates, conductors, and transducers. Additionally, we discuss the current state-of-the-art applications of nanomaterial-based wearable electronics and provide an outlook on future research directions in this field.